2018
DOI: 10.5539/ijef.v10n6p151
|View full text |Cite
|
Sign up to set email alerts
|

SME Financing in Africa: Collateral Lending vs Cash Flow Lending

Abstract: It is argued that economic growth in Africa will be enhanced by the expansion of small and medium-sized enterprises (SMEs) but these businesses face financing constraints which tend to hinder their business success. Starting from a discussion of the various sources of financing for SMEs in Africa, it is established that the most effective and cheapest source of capital for the SMEs is debt financing from banking and other microfinance institutions because of lender monitoring and the tax-deductibility of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Free-interest loans provided by the government may boost the starting operations of the organization. Most SMEs start businesses with private or personal savings or ask friends, family and relatives to make capital available in return for a profit or share in the business (Amoako-Adu and Eshun, 2018). If SMEs need more finance for expansion, innovation and survival, GS policies help them stand in the market (Ahlstrom et al , 2018).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Free-interest loans provided by the government may boost the starting operations of the organization. Most SMEs start businesses with private or personal savings or ask friends, family and relatives to make capital available in return for a profit or share in the business (Amoako-Adu and Eshun, 2018). If SMEs need more finance for expansion, innovation and survival, GS policies help them stand in the market (Ahlstrom et al , 2018).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…(Mukete et al, 2021 ; De Haas and Millone ( 2020 ) discovered that collateral and guarantee requirements may decrease during the course of the lending transaction. According to Amoako-Adu and Eshun ( 2018 ), collateral has been utilised to lessen the credit and information risks of SMEs. Naegels et al ( 2018 ) shown that collateral and guarantee should be the primary considerations for SME informal borrowing.…”
Section: The Setup Of Variables and Theoretical Frameworkmentioning
confidence: 99%
“…Fintech plays a crucial role in IFS, as stated by Correia et al ( 2022 ). Cash flow financing using big data analytics methodology may alleviate SME financial access difficulties, as it is based on SME cash flows, equity returns and value, and risk-sharing, according to Amoako-Adu and Eshun ( 2018 ). SME finance was analyzed by van Klyton and Rutabayiro-Ngoga ( 2018 ) using the k-score, which evaluates SME business networks on social media (Facebook, Twitter, and LinkedIn), emails, and mobile phones.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…In the absence of relevant information on SMEs, lenders can resort to collateral to mitigate risk. However, most African SMEs do not have adequate collateral (Amoako-Adu and Eshun, 2018). In the absence of adequate collateral, lenders tend to charge very high-interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%